Southern Ocean ice charts at the Argentine Naval Hydrographic Service and their impact on safety of navigation - Scardilli, Alvaro S.; Salvó, Constanza S.; Saez, Ludmila Gomez (Frontiers in Marine Science, 2022)
Antarctica is a largely inhospitable and inaccessible continent that plays a key role in regulating the climate through ocean currents, winds, icebergs drift, and sea-ice concentration and thickness. The study area of ​​this work corresponds to the Weddell Sea, Bellingshausen Sea and the South Atlantic Ocean. These areas are relevant because of supply operations to Antarctic stations and scientific and tourist activities. The Antarctic Peninsula is the most visited region of the continent for tourist and research vessels and requires special efforts in the development and dissemination of updated ice information for Safety of Navigation. For this purpose, it is critical to have information that discriminates the origin of the ice from land and open water, sea-ice concentration, and stage of development. The high recurrence of cloud cover over the Antarctic Peninsula during the summer hinders the operational use of visible/infra red satellite imagery, therefore access to Synthetic Aperture Radar (SAR) sensors is considered to be a high priority. Between 2018 and 2020, with the launch of the SAOCOM (Satélite Argentino de Observación Con Microondas) constellation, Argentina has evidenced an increase in the availability of SAR images for sea-ice operations. This paper presents the current state of routine production of operational ice charts at the Argentine Naval Hydrographic Service for mariners in the vicinity of the Antarctic Peninsula and South Atlantic Ocean and discuss future developments in place to prepare for expected increases in marine traffic in these areas.